Temporal Retrieval of LAI in the Wuding River Basin Based on a Hybrid Radiative Transfer Model (2001–2024) - Ma, Zhengze (Scientific Journal of Technology, 2026)
Leaf Area Index (LAI) is a key biophysical indicator characterizing vegetation canopy structure and ecosystem productivity. Focusing on the complex terrain of the Wuding River Basin in the Loess Plateau, this study performed LAI retrieval using remote sensing data from 2001 to 2024 combined with advanced algorithms.Based on the analysis of long-term time-series LAI data, this study revealed that LAI in the Wuding River Basin exhibited a distinct unimodal monthly growth rhythm: the peak value steadily occurred in July and August, the midsummer period with the most abundant hydrothermal conditions, while the trough value appeared in January and February during the vegetation dormancy stage.The results demonstrated that driven by the long-term implementation of ecological restoration projects, the vegetation canopy structure in the basin has been significantly improved, and the intra-annual fluctuation amplitude of LAI showed an expanding trend year by year, which accurately reflects the dynamic enhancement of radiative energy absorption capacity and transpiration intensity during the vegetation growing season.